Influence of Speed in Whole Body Vibration Exposure in Heavy Equipment Mining Vehicles. (September 2016) - Marin, Luz S.; Rodriguez, Andrés; Rey, Estefany; Barrero, Lope H.; Dennerlein, Jack; Johnson, Pete W.
This study aimed to characterize and contrast the ISO 2631-1 daily average-continuous A(8) and cumulative-impulsive VDV(8) whole body vibration (WBV) exposures during the operation of mining heavy equipment vehicles (HEVs). In a cross-sectional study, WBV measurements were collected from six different types of HEVs. For each HEV, the daily A(8) and VDV(8) WBV exposures were determined for each axis (x, y and z) along with the vector sum (∑xyx).. The predominant axis of vibration exposure was related to and dependent on the type of HEV, which all have different average speeds. Most of the predominant axis WBV exposures were above the ISO daily vibration action limits and the vector sum-based WBV exposures were considerably higher. Our results indicated that mining HEV operators are exposed to high levels of both continuous and impulsive WBV exposures, with the impulsive WBV exposures being more restrictive with respect the HEVs daily maximum operation hours.